Enantioselective pharmacokinetics of ketoprofen in calves after intramuscular administration of a racemic mixture. Issue 4 (20th November 2014) - Plessers, E.; Watteyn, A.; Wyns, H.; Pardon, B.; De Baere, S.; De Backer, P.; Croubels, S.
<x xml:space="preserve">Abstract</x> The pharmacokinetic properties of ketoprofen were determined in 4‐week‐old calves after intramuscular (i.m.) injection of a racemic mixture at a dose of 3 mg/kg body weight. Due to possible enantioselective disposition kinetics and chiral inversion, the plasma concentrations of the R(−) and S(+) enantiomer were quantified separately, using a stereospecific HPLC‐UV assay. A distinct predominance of the S(+) enantiomer was observed, as well as significantly different pharmacokinetic parameters between R(−) and S(+) ketoprofen. More in specific, a greater value for the mean area under the plasma concentration–time curve (AUC0→∞) (46.92 ± 7.75 and 11.13 ± 2.18 μg·h/mL for the S(+) and R(−) enantiomer, respectively), a lower apparent clearance (Cl/F) (32.8 ± 5.7 and 139.0 ± 25.1 mL/h·kg for the S(+) and R(−) enantiomer, respectively) and a lower apparent volume of distribution (Vd/F) (139 ± 14.7 and 496 ± 139.4 mL/kg for the S(+) and R(−) enantiomer, respectively) were calculated for the S(+) enantiomer, indicating enantioselective pharmacokinetics for ketoprofen in calves following i.m. administration.